Identifikasi Pasien COVID-19 Berdasarkan Riwayat Kontak - Arifin, Zaenal; Fatmawati, Baiq Ruli; Zuliardi, Zuliardi (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2020)
Background Covid-19 is a disease caused by a new corona virus called SARS-CoV-2. Human cases were first reported in Wuhan City, China in December 2019. Covid-19 has become a pandemic that has spread throughout the world including in Indonesia. The rapid spread of cases can be influenced by the mode of transmission of the virus which can be transmitted through direct contact with people who have been confirmed as Covid-19 or indirect transmission such as by air. The purpose of this study was to identify the characteristics of Covid-19 patients in Mataram City based on their previous contact history. Research Methods This study is a descriptive study using an observational approach. The sampling technique was carried out by total sampling and a sample of 286 Covid-19 cases was obtained, especially in Mataram City for the period of June 2020. Data collection was carried out through secondary data from the press release of the Covid-19 Task Force for West Nusa Tenggara Province about contact history. Results The study showed that there were 97 patients with Covid-19 in Mataram City who did not have a history of contact with Covid-19 patients (33.9%), 107 people with a history of contact with Covid-19 patients who had not been identified (37.4%). ), contacts with people without symptoms were 2 (0.7%), contacts with people with symptoms were 49 (17.4) and contact history with patients who were confirmed positive for Covid-19 were 31 people (10.8%). Conclusion Based on the results of research on the identification of Covid-19 cases in Mataram City in June 2020, in terms of contact history, it was found that some patients had a history of people who were detected as having Covid-19, whether they had not been identified, people without symptoms, people with symptoms and people who had confirmed Covid-19.